Endovascular conduit fenestration closure after extracardiac total cava-pulmonary anastomosis operation - Yu. L. Kuzmenko; A. V. Maksimenko; A. A. Dovgaluk; M. P. Radchenko; A. A. Motrechko (Ukrainian Journal of Cardiovascular Surgery, 2016)
This article represents the experience of percutaneous closure of extracardiac conduit fenestration in 6 patients after Fontan operation and detailed analysis of hemodynamic changes after the procedure.